Aluminum alloy material and aluminum alloy clad material

The aluminum alloy material with an intermetallic compound of Al, Si, and Sr addresses the trade-off between strength and melting point, achieving high strength and heat resistance while preventing brazing-related issues.

JP2025070742APending Publication Date: 2025-05-02MA ALUMINUM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023181257
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

There is a trade-off between achieving high strength and maintaining a suitable melting point in aluminum alloys, particularly when adding Si and Cu, which can lead to issues like buckling and erosion during brazing heat treatment.

Method used

The development of an aluminum alloy material with a composition that includes Al, inevitable impurities, and an intermetallic compound of Al, Si, and Sr, which maintains a melting point of 610°C or higher and a tensile strength of 150 MPa or higher after brazing equivalent heat treatment.

Benefits of technology

This solution effectively combines high strength and heat resistance in aluminum alloys, preventing issues like buckling and erosion during heat treatment while maintaining a suitable melting point.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070742000001
    Figure 2025070742000001
  • Figure 2025070742000002
    Figure 2025070742000002
  • Figure 2025070742000003
    Figure 2025070742000003
Patent Text Reader

Abstract

To provide an aluminum alloy material having high strength and excellent heat resistance.SOLUTION: An aluminum alloy material comprises Mn: 0.5 to 2.0%, Si: 0.6 to 1.2%, Cu: 0.01 to 1.0%, Fe: 0.05 to 1.0%, and Sr: 0.01 to 1.5%, with the balance being Al and unavoidable impurities. Observation in the material cross section (RD-ND plane) direction indicates the presence of intermetallic compounds made up of Al, Si, and Sr, which have a circle-equivalent diameter of 1 μm or more, in a number of more than 10 per 10000 μm2. The melting point (solidus temperature) is 610°C or higher. The tensile strength is 150 MPa or more after brazing-equivalent heat treatment.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy material and an aluminum alloy clad material. [Background technology]

[0002] As a means for improving the material strength of aluminum alloys for automotive heat exchangers, a technique of adding Mn, Si, and Cu is known (for example, Patent Document 1). Recently, there has been an increasing need for materials with low CO2 emissions. Although aluminum is a metal that does not emit much CO2 during the manufacturing process after casting, a large amount of CO2 is indirectly generated during the refining process, which requires a huge amount of electricity. Therefore, in order to produce low-CO2 materials, it is desirable to reduce the rate of new metal usage, i.e., to have a high recycling rate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-178170 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the more Si and Cu are added, the more the melting point of aluminum decreases. If the material's melting point drops, problems such as buckling and erosion occur during the brazing heat treatment. Therefore, there is a trade-off between high strength and low melting point, and it is necessary to develop technology that can achieve both.

[0005] The present invention has been made in light of the above circumstances, and has an object to provide an aluminum alloy material and an aluminum alloy clad material that combine high strength and heat resistance. [Means for solving the problem]

[0006] That is, the first embodiment of the aluminum alloy material of the present invention is an aluminum alloy material having a composition, by mass%, of 0.5-2.0% Mn, 0.6-1.2% Si, 0.01-1.0% Cu, 0.05-1.0% Fe, 0.01-1.5% Sr, and the balance being Al and unavoidable impurities, in which intermetallic compounds having Al, Si, and Sr as constituent elements have a circle equivalent diameter of 1 μm or more in an observation in the material cross section (RD-ND) direction, and 2 More than 10 particles are present per square inch, the melting point (solidus temperature) is 610°C or higher, and the tensile strength after heat treatment equivalent to brazing is 150 MPa or higher.

[0007] In another aspect of the invention, the aluminum alloy material of the above-mentioned aspect is characterized in that the content ratio of Si and Sr satisfies the relational formula of 1.56×Si>Sr in terms of mass ratio.

[0008] In another aspect of the invention, the aluminum alloy material of the above-mentioned aspect further contains, in the composition, one or more of Ti, V, Cr, Co, Ni, Y, Zr, Nb, and Mo in an amount of 0.35% by mass or less.

[0009] In another aspect of the invention, the aluminum alloy material of the above-mentioned aspect further contains, in the above-mentioned composition, one or two of Zn: 0.01-8.0% and Mg: 0.01-1.0%, by mass %.

[0010] The first embodiment of the aluminum alloy clad material of the present invention uses the aluminum alloy material of the above embodiment as a core material, and one or more layers of aluminum alloy material different from the above aluminum alloy material are bonded to one or both sides of the core material.

[0011] Another form of the invention of the aluminum alloy clad material has the aluminum alloy material of the above form as a skin material, and an aluminum alloy material of a different type from the above aluminum alloy material as a core material, with the skin material bonded to one or both sides of the core material.

[0012] The contents stipulated in the present invention will be explained below. Mn: 0.5-2.0% Mn is added to improve material strength by precipitating as intermetallic compounds such as Al-Mn, Al-Mn-Si, Al-Mn-Fe, and Al-Mn-Si-Fe. If the content is below the lower limit, the effect is insufficient, and if it exceeds the upper limit, coarse intermetallic compounds (crystallized products) are formed during casting, reducing rollability. For the same reason, it is preferable to set the lower limit at 0.7% and the upper limit at 1.8%.

[0013] Silicon: 0.6 to 1.2% Silicon is added to improve material strength by forming a solid solution, and also by precipitating as intermetallic compounds such as Al-Mn-Si and Al-Mn-Si-Fe. If the content is below the lower limit, the effect is insufficient, and if it exceeds the upper limit, the melting point of the material decreases.

[0014] Cu: 0.01 to 1.0% Cu is added to improve material strength by dissolving in solid solution. If the content is below the lower limit, the effect is insufficient, and if the content is above the upper limit, the material strength is too high, making it difficult to manufacture the material. For the same reason, it is preferable to set the lower limit at 0.3% and the upper limit at 0.8%.

[0015] Fe: 0.05 to 1.0 Fe is added to improve material strength by precipitating as intermetallic compounds such as Al-Mn-Fe and Al-Mn-Si-Fe. If the content is below the lower limit, costs will increase, and if it exceeds the upper limit, coarse intermetallic compounds (crystallized products) will form during casting, reducing rollability. For the same reason, it is preferable to set the lower limit at 0.1% and the upper limit at 0.75%.

[0016] Sr: 0.01 to 1.5% Sr is added to reduce the amount of dissolved Si in the base material by forming an intermetallic compound of Al-Si-Sr composition, and to increase the melting point of the base material. If the content is below the lower limit, the effect is insufficient, and if it exceeds the upper limit, coarse intermetallic compounds (crystallized products) are formed, reducing rollability. For the same reason, it is preferable to set the lower limit at 0.05% and the upper limit at 1.2%.

[0017] The mass ratio of Si and Sr satisfies the relationship 1.56Si>Sr. If Sr is added in excess of Si, the Sr becomes surplus, and the effect of increasing the melting point relative to the content is not obtained, and only the cost increases. In addition, there is a concern that the surplus Sr may become elements other than Si, or may become relatively coarse crystallized particles (not to a level that is unsuitable for manufacturing) by itself, causing holes when made into thin-walled materials such as fins. For these reasons, it is desirable to control the Si and Sr contents so that they satisfy a specified relationship.

[0018] One or more of Ti, V, Cr, Co, Ni, Y, Zr, Nb, and Mo: 0.35% or less These elements are optionally added in order to form intermetallic compounds and improve the strength of the material. If the content exceeds the upper limit, coarse intermetallic compounds are formed during casting, and rollability is reduced.

[0019] Zn: 0.01-8.0% Zn dissolves in the material to make its natural potential more base than other materials, and exerts a sacrificial anticorrosion effect. For example, when an aluminum alloy material is used as a constituent material of a clad material, it is optionally contained to improve pitting corrosion resistance. If the content is less than the lower limit, the effect is insufficient, and if it exceeds the upper limit, the potential becomes excessively base and the self-corrosion rate increases. For the same reason, it is preferable to set the lower limit at 0.5% and the upper limit at 6.5%. Zn may be contained in an amount of less than 0.01% as an inevitable impurity.

[0020] Mg: 0.01-1.0% Mg is optionally added to improve material strength by solid solution and by precipitating as an intermetallic compound such as Mg2Si to improve material strength. If the content is below the lower limit, the effect is insufficient, and if it exceeds the upper limit, the material strength is too high and it becomes difficult to manufacture the material. For the same reason, it is preferable to set the lower limit at 0.1% and the upper limit at 0.8%. Note that Mg may be contained in an amount of less than 0.01% as an inevitable impurity.

[0021] When observing the cross section (RD-ND) of the material, it was found that the intermetallic compounds consisting of Al, Si and Sr had a diameter of 1 μm or more in terms of circle equivalent diameter within 10,000 μm 2 More than 10 per By generating the Al-Si-Sr intermetallic compound, the amount of solute Si in the base material is reduced, and the melting point of the base material is increased. If the Al-Si-Sr intermetallic compound is too fine, it will re-dissolve during the brazing heat treatment. Also, if the specified distribution number is not obtained, the solute Si cannot be sufficiently reduced, and the effect of suppressing the decrease in the melting point cannot be obtained. For the same reason, the number is preferably 20 or more. The intermetallic compounds of Al-Si-Sr composition can be distributed in a specified size and number by controlling the cooling rate during casting, the homogenization treatment conditions, the temperature and time during hot rolling, and the reduction rate per pass during cold rolling.

[0022] Melting point: 610℃ or higher The melting point (solidus temperature) of the base material, which is primarily composed of aluminum, must be 610°C or higher. If the melting point is less than 610°C, excessive erosion occurs, resulting in significant deterioration of the properties.

[0023] Tensile strength after brazing is 150MPa or more Since the material according to the invention is used where high strength is required, the tensile strength after brazing must exceed 150 MPa, and for the same reason, it is preferably 160 MPa or more. The heat treatment conditions equivalent to brazing for measuring the tensile strength were heating to 600°C at an average heating rate of 100°C / min, holding at 600°C for 3 minutes, and then cooling to 150°C at a cooling rate of 100°C / min. However, the brazing heat treatment conditions of the present invention are not limited to these conditions.

[0024] Aluminum alloy clad material The aluminum alloy material of the present invention can be used alone, but can also be used as a constituent material of an aluminum alloy clad material bonded with other materials. In one embodiment, the aluminum alloy material of the present invention is used as a core material, and a skin material can be used on one or both sides of the core material. The skin material may be either a single layer or multiple layers, and the skin material may be of a different type having a composition and / or structure different from that of the aluminum alloy clad material of the present invention. When used as a core material, the material may be a single layer, or the material may be multi-layered, or the material may be multi-layered with another material. In another embodiment, the aluminum alloy material of the present invention can be used as a skin material for an aluminum alloy clad material. The core material can be a different aluminum material or aluminum alloy material from the aluminum alloy clad material of the present invention, and the present invention is not limited to a specific material for the core material. The aluminum alloy material of the present invention can be bonded to one or both sides of the core material. The aluminum alloy material can be a single layer or multiple layers. Effect of the Invention

[0025] According to the present invention, it is possible to obtain an aluminum alloy material and an aluminum alloy clad material having high strength and excellent heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] An embodiment of the present invention will be described below. The aluminum alloy material of the present invention can be manufactured through the steps of casting, homogenization treatment, facing, soaking, hot rolling, and cold rolling after being adjusted to have a composition as specified in the present application, and can be subjected to intermediate annealing and final annealing as necessary. There are no particular requirements for facing, soaking, intermediate annealing, or final annealing.

[0027] Casting and cooling rate Casting can be performed using semi-continuous casting or the like. There is no particular limitation on the casting method. The cooling rate during casting is preferably 0.1°C / s or more and less than 25°C / s. If the cooling rate during casting is below the lower limit, intermetallic compounds having Al, Si, and Sr as constituent elements will grow coarsely, resulting in reduced rollability. If the cooling rate exceeds the upper limit, it will be impossible to generate compounds in sufficient quantity and size. For the same reason, a cooling rate of 0.5°C / s or more and less than 15°C / s is preferable.

[0028] Homogenization After casting, it is desirable to carry out homogenization treatment. The homogenization treatment is desirably carried out at a temperature of 400°C or higher and lower than 620°C for 1 to 10 hours. By carrying out homogenization treatment under the above-mentioned specified conditions, the precipitation and growth of intermetallic compounds of Al-Si-Sr composition is promoted. If the temperature is lower than the lower limit, sufficient effect cannot be obtained, and if the temperature exceeds the upper limit, the material will melt. For the same reason, it is desirably 470°C or higher and lower than 600°C. The time is desirably 3 hours or more.

[0029] Temperature and time in hot rolling The rolling time at a material temperature of 400 to 500°C is preferably 3 minutes or more. By satisfying the predetermined rolling time at which dynamic strain is introduced in the above-mentioned predetermined high temperature range, the precipitation of intermetallic compounds of Al-Si-Sr composition of the predetermined size defined in the present invention is promoted. If the predetermined time is not met, sufficient effect cannot be obtained. For the same reason, 5 minutes or more is preferable.

[0030] Reduction per pass in cold rolling In cold rolling, the reduction rate per pass is preferably less than 60%. If it exceeds the upper limit, the intermetallic compound of Al-Si-Sr composition will be crushed finely, and the size of the compound will not be satisfied. For the same reason, it is preferable that it is less than 45%.

[0031] When the aluminum alloy material of the present embodiment is used as a constituent material of a clad material, the manufacturing process of the clad material is as follows: the skin material is cast, and if necessary, homogenized, surface-cut, and hot-rolled, and the core material and the skin material are assembled, and then the clad material is manufactured through soaking, hot rolling, and cold rolling. At this time, intermediate annealing and final annealing are performed if necessary. The manufacturing conditions of the clad rolling are the same as those described above.

[0032] Although the present invention has been described based on the above embodiment, appropriate modifications can be made to the above embodiment without departing from the scope of the present invention. EXAMPLES

[0033] Aluminum alloys with the composition shown in Table 1 (the balance being Al and unavoidable impurities) were prepared, and then cast, homogenized, faced, soaked, hot rolled, and cold rolled under the conditions shown in Table 2 to produce bare materials with a thickness of 0.07 mm and temper of H14, which were used as test materials (excluding materials for evaluating corrosion resistance).

[0034] Distribution of intermetallic compounds with Al, Si, and Sr as constituent elements The distribution of intermetallic compounds with Al-Si-Sr composition was evaluated for the obtained test materials. In the evaluation, the material cross section (RD-ND surface) was exposed by cross-section polishing, and a FE-EPMA (field emission electron probe microanalyzer) was used to perform fully automated particle analysis from the material cross section (RD-ND surface) direction to measure 10,000 μm 2 In the observation field, the number of intermetallic compounds whose constituent elements are Al, Si and Sr and have a circle equivalent diameter of 1 μm or more was counted by observing the material cross section (RD-ND plane) direction.

[0035] Melting Point Determination The melting points (solidus temperatures) of the test materials were measured using differential thermal analysis. The melting points of the test materials were evaluated into three levels: A, B, and C. A: 615℃ or higher is good B: 610℃ to 615℃, slightly better C: Less than 610℃ is defective

[0036] Material Strength After brazing-equivalent heat treatment, samples were cut out parallel to the rolling direction to prepare JIS No. 13 B test pieces, and tensile tests were performed. The brazing-equivalent heat treatment conditions were heating to 600°C at an average heating rate of 100°C / min, holding at 600°C for 3 minutes, and then cooling to 150°C at a cooling rate of 100°C / min. The material strength of each test material was evaluated on the following three levels: A, B, and C. A: 165MPa or more is good B: 150MPa or more but less than 165MPa is considered to be somewhat good. C: Less than 150MPa is defective

[0037] Corrosion resistance The test material was a 0.07mm thick aluminum alloy material with temper H14, corrugated to form a fin shape, assembled to a 0.2mm thick one-sided clad material (clad ratio 5%) with a filler metal of JISA4045 and a core metal of JISA3003, and brazed (brazing conditions were the same as above). A SWAAT corrosion test was performed, and the corrosion resistance was evaluated based on the corrosion depth of the clad material between the fins after 40 days of loading. The corrosion resistance of each test material was evaluated in two stages, A and C, as follows. A: Maximum corrosion depth of less than 80μm is good. C: 80μm or more is defective

[0038] Erosion resistance For test materials prepared under the same conditions as for corrosion resistance, the brazing filler erosion depth was evaluated by cross-sectional observation with an optical microscope. The erosion resistance of each test material was evaluated on the following three levels: A, B, and C. The brazing equivalent heat treatment is carried out under the same conditions as for material strength, and the brazing erosion depth is evaluated. A: Good if the erosion depth is less than 1 / 3 of the fin thickness. B: Between 1 / 3 and 2 / 3 of the plate thickness is slightly better C: Defective if deeper than 2 / 3 of the plate thickness

[0039] [Table 1]

[0040]

Table 2

[0041]

Table 3

[0042]

Table 4

[0043]

Table 5

[0044]

Table 6

Claims

1. The material contains, by mass%, 0.5-2.0% Mn, 0.6-1.2% Si, 0.01-1.0% Cu, 0.05-1.0% Fe, 0.01-1.5% Sr, with the balance being Al and unavoidable impurities. When observed in the cross section (RD-ND) direction of the material, 10,000 μm of intermetallic compounds having Al, Si, and Sr as constituent elements have a circle equivalent diameter of 1 μm or more. 2 an aluminum alloy material having more than 10 particles per square inch, a melting point (solidus temperature) of 610°C or higher, and a tensile strength of 150 MPa or higher after heat treatment equivalent to brazing.

2. The aluminum alloy material according to claim 1, wherein the content ratio of Si and Sr satisfies the relational expression of 1.56×Si>Sr in terms of mass ratio.

3. 3. The aluminum alloy material according to claim 1 or 2, further comprising, in mass%, 0.35% or less of one or more of Ti, V, Cr, Co, Ni, Y, Zr, Nb, and Mo.

4. The aluminum alloy material according to claim 1 or 2, further comprising, in mass%, one or two of Zn: 0.01 to 8.0% and Mg: 0.01 to 1.0%.

5. The aluminum alloy material according to claim 3, further comprising, in mass%, one or two of Zn: 0.01 to 8.0% and Mg: 0.01 to 1.0%.

6. 3. An aluminum alloy clad material comprising the aluminum alloy material according to claim 1 or 2 as a core material, and one or more layers of an aluminum alloy material different from the aluminum alloy material bonded to one or both sides of the core material.

7. 4. An aluminum alloy clad material comprising the aluminum alloy material according to claim 3 as a core material, and one or more layers of an aluminum alloy material different from the aluminum alloy material bonded to one or both sides of the core material.

8. 5. An aluminum alloy clad material comprising the aluminum alloy material according to claim 4 as a core material, and one or more layers of an aluminum alloy material different from the aluminum alloy material bonded to one or both sides of the core material.

9. 6. An aluminum alloy clad material comprising the aluminum alloy material according to claim 5 as a core material, and one or more layers of an aluminum alloy material different from the aluminum alloy material bonded to one or both sides of the core material.

10. 3. An aluminum alloy clad material comprising the aluminum alloy material according to claim 1 or 2 as a skin material, an aluminum alloy material different from the aluminum alloy material as a core material, and the skin material bonded to one or both sides of the core material.

11. 4. An aluminum alloy clad material comprising the aluminum alloy material according to claim 3 as a skin material, an aluminum alloy material different from the aluminum alloy material as a core material, and the skin material bonded to one or both sides of the core material.

12. 5. An aluminum alloy clad material comprising the aluminum alloy material according to claim 4 as a skin material, an aluminum alloy material different from the aluminum alloy material as a core material, and the skin material bonded to one or both sides of the core material.

13. 6. An aluminum alloy clad material comprising the aluminum alloy material according to claim 5 as a skin material, an aluminum alloy material different from the aluminum alloy material as a core material, and the skin material bonded to one or both sides of the core material.

Citation Information

Patent Citations

  • Thin wall fin material excellent in erosion resistance, manufacturing method of thin wall fin material excellent in erosion resistance, and manufacturing method of heat exchanger

    JP2018178170A